Building moderate attitude and intercultural competence in literature classes: Teachers’ experience at higher education institutions - Syafiyah, Syafiyah; Degaf, Agwin; Irham, Irham; Huda, Miftahul (Universitas Islam Negeri Banda Aceh, 2022)
Foreign language teaching is a medium to raise students’ inter-cultural understanding, awareness, and sensitivity important for establishing tolerant mindset in multi-ethnic community. However, the use of literary works in foreign language teaching, for example TESOL, which could elevate intercultural competence since they promote respect and appreciation, is almost unexplored. This paper examined to which extent the values of moderation are presented during the teaching of literature and explicated in the curriculum, as well as the course outline of literary courses in three participating Indonesian Islamic Universities. This case study research collected data through a semi-structured interview with three lecturers English Literature Department, Walian University (pseudonym) administered under Indonesian Ministry of Religious Affairs and were analysed through critical exploratory lens. The results demonstrate that lecturers face complex issues regarding the incorporation and promotion of moderation values during the teaching of literature. Yet, the curriculum, on the other hand, has not embedded those values but are manifested in the teaching and learning process from the selection of teaching materials or learning activities. The lecturers remain the main actors in uplifting the introduction of moderate attitude during the teaching of literature.